EFFECT OF URBANIZATION ON CHANNEL PLATFORMS OF RIVER KADUNA FROM 1962-2017, KADUNA STATE, NIGERIA - Butu, Ali Williams; Emeribe, Chukwudi Nnaemeka; Leke, Dewingong Columbus; Jibril, Mamman Shaba (Jurnal Geografi Lingkungan Tropik (Journal of Geography of Tropical Environments), 2020)
The study investigated changes in channel planforms of River Kaduna. Topographic maps were complimented with Mosaic of SPOT 5 satellite and Sentinel-2 images. Results showed that except for sinuosity index and channel length, channel width, braiding and channel migration exhibited considerable changes. These changes were evident in reduced velocity and stream energy, the type of sediment being transported, the silt materials being transported in suspension and the coarse sand and gravels being moved by lift and drag processes which are easily deposited, thus causing the channel to contract and braid. Channel migration occurred as gradual bend shifts leaving no evidence of lateral abrasion. Similarly, channel length did not change significantly to affect the sinuosity index. The result further revealed there was little lateral abrasion and the channel are relatively stable, implying that the materials being transported and deposited must have originated from the watershed. Anthropogenic factors such as urbanization, deforestation and agriculture activities contributed significantly to the observed channel alteration. There is a need to encourage mining gravel and sand from braided channels to provide sinks for sediments that otherwise would be deposited downstream. Afforesting the catchment area is required to create canopies to exposed surface and reduce sediment supplies.